Stakeholder trust in family businesses - Hauswald, Hannes (Familienunternehmen und KMU, 2013)
Despite broad anecdotal evidence, little is known about the drivers of stakeholder trust in family businesses and relevant outcomes. The topic has received little systematic attention, which is surprising given its importance as a potential competitive advantage for family businesses and the significant role of family businesses in many markets around the world. Hannes Hauswald addresses this gap. In the course of three essays, he explores the antecedents of stakeholder trust when dealing with family businesses. Furthermore, he sheds light on the outcomes of stakeholder trust for family businesses as well as on relevant contingency factors. Contents ·         Antecedents and Outcomes of Stakeholder Trust in Family Businesses: An Application of the Integrative Model of Organizational Trust ·         The Influence of Family Ownership on Stakeholders' Perceptions of Trustworthiness ·         Family Businesses' Ability to Attract New Talent: Who is Attracted and Under What Conditions?    Target Groups ·        Researchers and students in the fields of family business research, trust research, and stakeholder management research ·         Managers and owners of family businesses as well as all relevant stakeholder groups of these firms, such as customer, suppliers, or employees     The Author Dr. Hannes Hauswald wrote his dissertation under the supervision of Prof. Dr. Andreas Hack at the INTES Institute for Family Businesses at WHU - Otto Beisheim School of Management, Vallendar.     About the Editors The series Familienunternehmen und KMU is edited by Prof. Dr. Andreas Hack, Prof. Dr. Andrea Calabrò, Prof. Dr. Hermann Frank, Prof. Dr. Franz W. Kellermanns Ph.D. and Prof. Dr. Thomas Zellweger.